Pengaruh Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Jasa Car Wash: Studi Kasus Sakti Carwash Kota Binjai - Yudi Bimantaka; Sri Ramadhani; Nurwani (Economic Reviews Journal, 2024)
This research aims to determine the influence of service quality and price on purchasing decisions for car wash services among Sakti Carwash consumers in the city of Binjai. This research uses a quantitative approach with an associative research approach. Data collection techniques were carried out using questionnaires, observation and documentation methods. The sample used was 97 people who were Sakti Carwash Binjai consumers taken using probability sampling techniques. The data analysis technique in this research uses multiple linear regression analysis with hypothesis analysis using the partial test (t), simultaneous test (F), and coefficient of determination test (Ajusted R2) which is processed using the IBM SPSS version 25 application. The results of this study show that the quality service and price partially have a positive and significant effect on purchasing decisions. Service quality and price together (simultaneously) have a positive and significant effect on purchasing decisions.